O Horizonte Político de Guicciardini: entre Maquiavel e Giannotti - Marin, Marcelo de Paola (2017)
This thesis aims at presenting Francesco Guicciardini and the importance of his works to the Political Philosophy, starting from the thinker´s life, political path, influence and works. Throughout the thesis, we will analyze the political components of Guicciardini´s works, concepts and practice as well as their intersections with the works of other contemporary thinkers, who had the Florentine Policy as their object of study. Above all, the objective of this thesis is to learn about the Guicciardini’s analysis and its conceptual elements, which contributed to the understanding of the political fact and its social and institutional mechanisms. Based on the works of Francesco Guicciardini, the present thesis aims at revealing the way politics must be performed in the republican context, by recognizing, as role models, the political thinkers' reflections on the Florentine Republic in the fifteenth and sixteenth centuries, the citizenship exercise and the preservation of common good. We particularly focus on the thoughts of Francesco Guicciardini, an attentive reader of both the political works of his time and of the classical antiquity, who analyzes the time when he lived as an intellectual and a "man of political praxis". His works enable a better understanding of Machiavel´s political thought, as Guicciardini had the privilege to follow Machiavel and share ideas with him. In an original manner, the political work of Guicciardini becomes extremely relevant to the Contemporary Political Philosophy, once it talks about issues which are also found in the Florentine Secretary´s works. This enables a qualified study of the Republicanism within the Florentine Civic Humanism